Achievement of diffusional independence at nanoscale liquid-liquid interfaces within arrays - Liu, Yang; Sairi, M.; Neusser, G.; Kranz, C.; Arrigan, Damien (American Chemical Society, 2015)
In this work, independent radial diffusion at arrayed nanointerfaces between two immiscible electrolyte solutions (nanoITIES) was achieved. The arrays were formed at nanopores fabricated by focused ion beam milling of silicon nitride (SiN) membranes, enabling the reproducible and systematic design of five arrays with different ratios of pore center-to-center distance (rc) to pore radius (ra). Voltammetry across water–1,6-dichlorohexane nanoITIES formed at these arrays was examined by the interfacial transfer of tetrapropylammonium ions. The diffusion-limited ion-transfer current increased with the ratio rc/ra, reaching a plateau for rc/ra ≥ 56, which was equivalent to the theoretical current for radial diffusion to an array of independent nanoITIES. As a result, mass transport to the nanoITIES arrays was greatly enhanced due to the decreased overlap of diffusion zones at adjacent nanoITIES, allowing each interface in the array to behave independently. When the rc/ra ratio increased from 13 to 56, the analytical performance parameters of sensitivity and limit of detection were improved from 0.50 (±0.02) A M–1 to 0.76 (±0.02) A M–1 and from 0.101 (±0.003) μM to 0.072 (±0.002) μM, respectively. These results provide an experimental basis for the design of arrayed nanointerfaces for electrochemical sensing.